The Effect of Constitutional Court Decision Number 19/PUU-XX/2022 on Tax Fairness and Compliance among Business Entities in Indonesia - Judijanto, Loso; Heriyanto, Heri (West Science Law and Human Rights, 2024)
The Indonesian Constitutional Court's Decision Number 19/PUU-XX/2022 has significant implications for tax fairness and compliance among business entities in Indonesia. This research employs a qualitative approach to explore the multifaceted effects of this decision on tax-related behaviors and perceptions within the Indonesian business community. Through in-depth interviews, thematic analysis, and theoretical frameworks, this study aims to provide insights into how constitutional court decisions shape tax compliance and fairness perceptions in a developing economy like Indonesia. The findings of this research contribute to the understanding of legal influences on tax behavior and inform policy recommendations aimed at enhancing tax compliance and fairness in Indonesia.